Doa terakhir : antologi puisi dan cerpen hadiah sastera Malaysia, 1988/89 - T. Alias Taib. (Kuala Lumpur : Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1995)
Collection of Malaysian prize winning poems and short stories.
In Malay.
Keywords: Malay literature -- Collections